PREFERENCE OF TEACHING AND LEARNING METHODS IN A MEDICAL SCHOOL OF INDIA - PREETY LACHHIRAMKA; SUJAY PATIL; PRAMILA YADAV (International Journal of Pharma and Bio Sciences, 2016)
Teaching and learning are self-evolving process. There is a strong correlation between the methods used in transforming information by the lecturer’s and assimilation of knowledge of the students. Purpose of this study is to assess the teaching and learning expectations of the medical students from the lecturer and the institution. A questionnaire based study was carried out at DYPUSM, Navi Mumbai. MBBS students studying in Phase 2 were enrolled in study after taking informed consent. 100 students were selected randomly out of 150 Phase 2 medical students from Batch 2015 to answer the questionnaire study. Study was conducted on 20 October 2015. The main teaching and learning methods for pre-clinical phase includes lecture, tutorial, practical, problem based learning (PBL) and early clinical exposure (ECE). Validated and pretested questionnaire was obtained after taking permission from authors who carried out a similar study in Malaysia. Questionnaire was divided into 7 sections. Data was analyzed using appropriate statistical tests. This study showed that 37 (37 %) out of 100 respondents chose a lecture as most preferred teaching and learning method. Other methods favored are problem-based learning 20 (20 %), early clinical exposure 1 (18 %), practical 10 (10 %), tutorial 8 (8 %) and computer learning activity 7 (7 %). Most preferred methods were lecture and problem-based learning to acquire knowledge in a medical school. Final outcome of this study would definitely help medical universities in improving learning and teaching methodologies which would contribute towards development of knowledgeable and highly skilled medical graduates.